HBx-induced PLA2R overexpression mediates podocyte pyroptosis through the ROS-NLRP3 signaling pathway - Moxuan Feng; Yani Yu; Yueqi Chen; Xiaoqian Yang; Baoshuang Li; Wei Jiang (Renal Failure)
Introduction Hepatitis B virus-associated glomerulonephritis (HBV-GN) is one of the main types of secondary glomerular diseases, and podocyte injury is an important pathogenic mechanism of HBV-GN, participating in the occurrence and development of HBV-GN. However, the specific mechanism of podocyte injury remains to be studied.Methods Human renal podocytes cultured in vitro were divided into six groups. The podocyte morphology was observed under a transmission electron microscope, and the expression of M-type phospholipase A2 receptor (M-PLA2R) on the podocyte membrane was observed by indirect immunofluorescence staining under a fluorescence microscope. The pyroptosis rate and reactive oxygen species (ROS) of podocytes were assessed by FLICA/PI double staining and flow cytometry. Western blot (WB) and quantitative real-time PCR (qPCR) were used to determine the expression of PLA2R, nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3), apoptosis-associated speck-like protein containing card (ASC), caspase-1, IL-1β, and IL-18.Results Hepatitis B virus X (HBx) transfected into human renal podocytes in vitro induced the overexpression of PLA2R. Moreover, the overexpressed PLA2R combined with secretory phospholipase A2 group IB (sPLA2-IB) aggravated podocyte injury and increased the pyroptosis rate. In addition, the expression of ROS, the NLRP3 inflammasome and downstream inflammatory factors was increased. In contrast, after inhibiting the expression of PLA2R and ROS, podocyte damage was alleviated, and the pyroptosis rate and the expression of genes related to the ROS-NLRP3 signaling pathway were decreased.Conclusion HBx-induced PLA2R overexpression on the podocyte membrane can significantly upregulate the ROS-NLRP3 signaling pathway, thereby mediating podocyte pyroptosis.